Mycorrhizal fungi symbiosis as a strategy against oxidative stress in soybean plants - Bressano, Marina (2010)
Oxidative stress responses generated by paraquat (PQ), an herbicide that triggers an oxidative stress reaction in leaves, were studied in non-arbuscular mycorrhizal (non-AM) and in arbuscular mycorrhizal (AM) soybean plants inoculated with Glomus mosseae (Gm) or Glomus intraradices (Gi). Some oxidative stress symptoms were evident in non-AM after 6 d of PQ application on leaves. Oxidative damage, measured as malondialdehyde content (MDA), was significantly higher, and although no changes were evident in total catalase (CAT, EC 1.11.1.6) and total superoxide dismutase (SOD, EC 1.15.1.1) activity, total ascorbate peroxidase (APX, EC 1.11.1.11) activity was significantly reduced. These effects were correlated with a significant decrease in growth parameters. By contrast, in both AM plants, foliar MDA content was reduced or unaltered and, interestingly, after PQ stress, its level was unchanged and significantly lower than in PQ non-AM plants. Unlike PQ stress in non-AM plants, total APX activity was unaltered or induced by AM plants, while total SOD activity was unchanged and no consistent effects were detected in total CAT activity. All these events coincided with no changes or a significant increase in growth parameters. Since oxidative stress is a common phenomenon triggered by several environmental stresses, these results highlight the importance of mycorrhizal fungi in oxidative stress regulation as a general strategy to protect plants from abiotic and biotic stress.